Topographic shading influences cryoconite morphodynamics and carbon exchange. Issue 1 (1st January 2018) - Cook, J. M.; Sweet, M.; Cavalli, O.; Taggart, A.; Edwards, A.
ABSTRACT: Cryoconite holes are the most active and diverse microbial habitats on glacier and ice-sheet surfaces. In this article the authors demonstrate that the shape of cryoconite holes varies depending on ice-surface topography and that this has implications for the carbon cycling regime within. Net ecosystem production is shown to be controlled primarily by sediment thickness within holes. The authors show that irregular hole shapes are indicative of hole migration away from topographic shade, which promotes carbon fixation at the mesoscale on ice surfaces. A cellular automaton is used in conjunction with sediment-delivery experiments to show that migration is the result of simple sediment transfer processes, implying a relationship between ice-surface evolution and cryoconite biogeochemistry that has not previously been examined.